Problems and Challenges of Learning Through a Second Language: The Case of Teaching of Science and Mathematics in English in the Malaysian Primary Schools - Tan Yao Sua; Santhiram R. Raman (Kajian Malaysia, 2007)
In 2003, there was a significant change in the language policy in the Malaysian education system whereby the Malaysian government decided to introduce English as a language medium to teach science and mathematics at all levels of the education system in stages. The aim of the policy was to arrest declining standards of English among Malaysian students. The implementation of this policy was most contentious at the primary school level involving two different models of implementation: bilingual model for the Chinese primary school and maximum exposure model for the national school and the Tamil primary school. This paper examines the problems and challenges of implementing the policy of teaching science and mathematics in English in the Malaysian primary schools, which entails learning through a second language. It looks at some of the theoretical constructs pertaining to choice of language as well as learning through a second language. These theoretical constructs offer some perspective lights on the implementation of the policy of teaching science and mathematics in English in the Malaysian primary schools by highlighting its strengths and weaknesses. Based on these theoretical constructs, this paper posits the bilingual model adopted by the Chinese primary schools as a better model to facilitate learning through a second language during the early years of schooling.